Mobile networks and management : 7th International Conference, MONAMI 2015, Santander, Spain, September 16-18, 2015, Revised selected papers /: 7th International Conference, MONAMI 2015, Santander, Spain, September 16-18, 2015, Revised selected papers. (2015) - Unknown
No abstract available